ACT-26 PATTERN OF RECURRENCE IN NEWLY DIAGNOSED GLIOBLASTOMA TREATED WITH PHOTODYNAMIC THERAPY. (3rd December 2022) - Nakayama, Noriyuki; Yamada, Tetsuya; Ohe, Naoyuki; Yano, Hirohito; Iwama, Toru
Abstract: In 2016, photodynamic therapy (PDT) system using talaporfin sodium was introduced to our hospital. By December 2021, we have experienced 22 cases (15 males, 7 females, 57.9±18.6 years old) of newly diagnosed glioblastoma (GBM) treated with PDT. The recurrence pattern of 22 cases was retrospectively examined. In August 2022, 7 cases are still alive. Laser irradiation was performed at an average of 7.6±3.4 sites. Tumor localization was solitary and superficial in 14 cases. Extent of tumor resection was 89.3±18.5%, and the postoperative KPS was 86.4±15.0%. Median PFS was 11 months, median OS was 18 months, and 5 patients survived for more than 3 years. Recurrences were observed in 16 cases, and the recurrence types were local (LR) in 9 cases, distant (DR) in 3 cases, and both in 4 cases. Two of the remaining 6 cases, which were judged to have no recurrence at present, had Gd-enhancing lesions locally and were judged to have LR. Therefore, re-resection was performed in both cases, but the pathological diagnosis was gliosis. Fujita et al. (J Neurooncol 155:81-92, 2021) reported that acute response of high-grade glioma to PDT can be detected as linear transient hyperintense signal (LTHS) on diffusion-weighted imaging (DWI), and that All of the LRs arose from areas that did not show LTHS on DWI obtained on day 1 after PDT. Furthermore, they reported that this characteristic finding is useful for monitoring LR after PDT. In our cases, 3 DRs and 4 existing long-term survivors (including 2 with local gliosis) showed nearly LTHS throughout the resected wall. On the other hand, partial absence of LTHS was confirmed in 13 cases containing LR. PDT provides effective local control, but it requires careful irradiation planning to avoid missing areas of irradiation, and LTHS on DWI could indicate whether effective irradiation has been achieved.